Presencia de haplotipos no africanos incrementa la diversidad genética en pacientes con anemia falciforme en Colombia (2018)
The objective of this study was identify the frequency of Beta globin cluster’s haplotypes present in sickle cell anemia patients in Colombia, to establish the presence of non-African haplotypes in this population, to verify variations in the pattern of linkage disequilibrium in the Beta globin cluster. It was analyzed 83 individuals affected with sickle cell anemia, the haplotypes were formed using five restriction sites into Beta globin cluster. The haplotype frequency was calculated, as well as the linkage disequilibrium among restriction sites, the genetic similarity among Colombian population and other affected American population was determined. The haplotypes most frequent were Benin (35.1 %) and Bantu (26.5 %), both African. However, haplotypes present in American indigenous and European populations got frequency between two to ten percent, as well as haplotypes not reported in others population were observed in our population. The restriction sites showed low or null linkage disequilibrium. When compare with other populations, the Colombian population showed higher similarity with Venezuelan population where Benin and Bantu are predominant too. Our results showed that admixture has facilitated the move of sickle cell mutation to a non-African genetic context (Amerindian and European). Further, the admixture has also modified the pattern of linkage disequilibrium into the Beta globin cluster generating modifications that could have influence in association studies in this affected population. © 2018, Universidad Nacional de Colombia. All rights reserved.